CO2 induced changes in Mount Simon sandstone: Understanding links to post CO2 injection monitoring, seismicity, and reservoir integrity. (September 2020) - Harbert, William; Goodman, Angela; Spaulding, Richard; Haljasmaa, Igor; Crandall, Dustin; Sanguinito, Sean; Kutchko, Barbara; Tkach, Mary; Fuchs, Samantha; Werth, Charles J.; Tsotsis, Theodore; Dalton, Laura; et al.
Highlights: The purpose of this study is to quantify geochemical reactions of CO2 and brine with subsurface samples taken from the Mt. Simon sandstone and identify any potential alterations of the geomechanical rock properties that could lead to changes observable in seismic monitoring or result in changes of micro seismicity. Changes in porosity, permeability, dynamic mineral framework moduli, and brittleness with exposure to these fluids were observed. These observations could provide insight into subsurface monitoring using seismic methods including amplitude variation with offset (AVO) classification. Abstract: The purpose of this study is to quantify geochemical reactions of CO2 and brine with subsurface samples taken from the Mt. Simon sandstone and identify any potential alterations of the geomechanical rock properties that could lead to changes observable in seismic monitoring or result in changes of micro seismicity such as those observed at the Illinois Basin-Decatur Project (IBDP) site. Two Mt. Simon sandstone samples from 6919.3 feet (2109.0 m) and 6926.1 feet (2111.1 m) depth were exposed to supercritical CO2 (scCO2 ) dissolved in brine at in-situ reservoir conditions for one month. Geochemical, spectral, scanning electron microscopy, and petrophysical methods were used to analyze the samples before and after the one-month exposure. Significant changes were observed. Multiple geomechanical properties were chosen to form the framework against which to interrogate the petrophysical data: Young's modulus (E), Poisson's ratio ( ν ), lambda·rho (λρ), and mu·rho (μρ). In this study we conclude that framework composition, porosity, heterogeneities, effective pressure, and reactive geochemistry are first order controls on trends in the E-μ and λρ-μρ cross plot spaces. Changes in porosity, permeability, dynamic moduli, and brittleness with exposure to these fluids were observed. No change in ultrasonic P-wave attenuation (QP ) was observed. Geochemical alteration causes a distinct shift in λρ-μρ in both samples as well as changes in E, ν , and P and S wave seismic velocity values. These observations could provide insight into subsurface monitoring using seismic methods including amplitude variation with offset (AVO) classification.